ANALISIS KESEHATAN LINGKUNGAN RUMAH DENGAN KEJADIAN TUBERKULOSIS DI DESA TANJUNG SETEKO KECAMATAN INDRALAYA KABUPATEN OGAN ILIR - Oktriyedi, Ferly; Fauta, Ari; Agustin, Agustin (Journal Safety and Healthty, 2024)
The World Health Organization (WHO) states Tubercullosis (TB) is a very important and serious public health problem worldwide. The purpose of this study was to analyze the occurrence of tuberculosis (TB). This research was conducted in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency from September 2020 to February 2021. This type of research used an analytical survey with a cross sectional approach. The sample in this study was the people of Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency and the sample was taken by simple random sampling totaling 142 respondents. Statistical test on bivariate using chi-square test and multiple logistic regression with confidence level =95%. The results showed that there was a significant relationship between temperature, humidity, ventilation, occupancy density, type of house floor, type of house wall, ceiling height and the incidence of Tuberculosis (TB) in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency in 2021 and the dominant one was ventilation. Suggestion In an effort to reduce the incidence of Tuberculosis (TB) in the village, it is necessary to carry out socialization in the form of counseling to families which aims to increase knowledge, attitudes and behavior of the community in preventing the incidence of Tuberculosis (TB). Conducted outreach to the community about maintaining a good temperature for the prevention of Tuberculosis (TB).